Bifurcation phenomena for incompressible laminar flow in expansion channel to study Coanda effect. Issue 2 (17th February 2020) - Saha, Sandip; Biswas, Pankaj; Nath, Sujit
Abstract: The present study analyzes the symmetry breaking and Hopf bifurcation of incompressible laminar flow through two-dimensional expansion channel with different expansion ratios. The governing momentum and mass conservation equations are solved by SIMPLE algorithm (pressure based solver) in Ansys workbench 14.1. It investigates the values of critical Reynolds number for symmetry breaking bifurcation and Hopf bifurcation using three different mesh refinements. Three different types of expansion channels have been used to analyze the bifurcation phenomena. The flow is assumed to be viscous, unsteady, laminar and Newtonian. It is observed that increase in expansion ratio causes a decrease of critical Reynolds number (Recr ).